The 2014 coral bleaching and freshwater flood events in Kāneʻohe Bay, Hawaiʻi - Keisha D. Bahr; Paul L. Jokiel; Kuʻulei S. Rodgers (PeerJ, 2015)
Until recently, subtropical Hawaiʻi escaped the major bleaching events that have devastated many tropical regions, but the continued increases in global long-term mean temperatures and the apparent ending of the Pacific Decadal Oscillation (PDO) cool phase have increased the risk of bleaching events. Climate models and observations predict that bleaching in Hawaiʻi will occur with increasing frequency and increasing severity over future decades. A freshwater “kill” event occurred during July 2014 in the northern part of Kāneʻohe Bay that reduced coral cover by 22.5% in the area directly impacted by flooding. A subsequent major bleaching event during September 2014 caused extensive coral bleaching and mortality throughout the bay and further reduced coral cover in the freshwater kill area by 60.0%. The high temperature bleaching event only caused a 1.0% reduction in live coral throughout the portion of the bay not directly impacted by the freshwater event. Thus, the combined impact of the low salinity event and the thermal bleaching event appears to be more than simply additive. The temperature regime during the September 2014 bleaching event was analogous in duration and intensity to that of the large bleaching event that occurred previously during August 1996, but resulted in a much larger area of bleaching and coral mortality. Apparently seasonal timing as well as duration and magnitude of heating is important. Coral spawning in the dominant coral species occurs early in the summer, so reservoirs of stored lipid in the corals had been depleted by spawning prior to the September 2014 event. Warm months above 27 °C result in lower coral growth and presumably could further decrease lipid reserves, leading to a bleaching event that was more severe than would have happened if the high temperatures occurred earlier in the summer. Hawaiian reef corals decrease skeletal growth at temperatures above 27 °C, so perhaps the “stress period” actually started long before the bleaching threshold of 29 °C was reached. Hawaiʻi is directly influenced by the PDO which may become a factor influencing bleaching events in subtropical Hawaiʻi in much the same manner as variations in the El Niño Southern Oscillation (ENSO) influences bleaching events at low latitudes in the tropical Pacific. Records show that offshore temperatures measured by satellite will not always predict inshore bleaching because other factors (high cloud cover, high wind and wave action, tidal exchange rate) can limit inshore heating and prevent temperatures in the bay from reaching the bleaching threshold. Low light levels due to cloud cover or high turbidity can also serve to prevent bleaching.